\[\boxed{\mathbf{721\ (721).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[a_{8} = 3,\ \ a_{9} = - 12\]
\[a_{9} = a_{8} + d\ \ \]
\[d = a_{9} - a_{8} = - 12 - 3 = - 15.\]
\[\boxed{\mathbf{721.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[a^{2n + 1} + 1 =\]
\[= (a + 1) \cdot\]
\[\cdot \underset{геометрическая\ прогрессия}{\overset{(a^{2n} - a^{2n - 1} + \ldots + a^{2} - a + 1)}{︸}}\]
\[b_{1} = - 1 \Longrightarrow \ \ q = - \frac{a}{1} = - a\]
\[a^{2n} = b_{1}q^{x - 1} = bn\]
\[a^{2n} = 1 \cdot ( - a)^{x - 1}\text{\ \ }\]
\[a^{2n} = ( - {a)}^{2n}\ \text{\ \ }\]
\[так\ как:\]
\[2n - четная\ степень,\ тогда\]
\[\text{\ \ }( - {a)}^{2n} = ( - a)^{x - 1}\ \]
\[2n = x - 1;\ \ \ \ x = 2n +\]
\[+ 1 \Longrightarrow количество\ всех\ \]
\[членов\ прогрессии.\]
\[S_{2n + 1} = \frac{b_{1} \cdot \left( q^{2n + 1} - 1 \right)}{q - 1} =\]
\[= \frac{1 \cdot \left( ( - a)^{2n + 1} - 1 \right)}{- a - 1} =\]
\[= \frac{- a^{2n + 1} - 1}{- (a + 1)} = \frac{- \left( a^{n + 1} + 1 \right)}{- (a + 1)} =\]
\[= \frac{a^{n + 1} + 1}{a + 1}\]
\[a^{2n + 1} + 1 = (a + 1) \cdot \frac{a^{n + 1} + 1}{a + 1}\text{\ \ }\]
\[a^{2n + 1} = a^{2n + 1} \Longrightarrow доказано.\]